Economic Exclusion of Refugees and Strategies of Resistance: A Case Study of Syrian refugees living in Jordan - Ola MAJTHOUB (Košická bezpečnostná revue)
This study sheds light on the mechanisms of social exclusion faced by Syrian refugees living in Mafraq, Jordan, as well as the defensive tactics they have developed in response. The study focuses on the economic aspect of exclusion and the challenges Syrian refugees face in accessing the labor market and maintaining their professions. Drawing upon Bourdieu’s field theory and Michel de Certeau’s notions of "strategy" and "tactics," the study endeavors to elucidate the everyday experiences of Syrians in Mafraq, Jordan. Employing a qualitative research methodology, the study engaged in face-to-face interviews with thirteen Syrian individuals residing in the Mafraq governorate. Through these interviews, the subjective perceptions of Syrians regarding their encounters with economic exclusion in everyday life were explored. The findings unearthed a multifaceted array of challenges encountered by Syrian refugees. The research unveiled the emergence of resistance tactics among the refugee population as a response to the dynamics of economic exclusion. These tactics serve as a means for refugees to navigate and confront the barriers erected by their marginalized status. The results highlight the importance of addressing these issues through effective policies and practices to promote social integration and the well-being of Syrian refugees in Jordan